Pertanggungjawaban Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Pencurian - Febriyandi, Hardiki; Surahman, Surahman (Bacarita Law Journal, 2024)
The theft committed by children must have several factors, namely several economic components or factors, parents because they do not pay attention to their children and thus commit acts against the law, social factors, and mass media factors. A child is a person who is not yet competent or a minor. What is called a child is a child who is not yet 18 years old and includes shildren who are still in the womb. This research aims to find out who is legally responsible for violations committed by children of theft according to Indonesian law, the factors that cause theft in cases involving Decision Number 1/Pid.Sus-Anak/2023/Pn Bpp. A normative approach, such as literature research based on laws and cases, is used in this research, these legal resources are classified into primary, secondary and tertiary. The results of this research are that children must be able to take responsibility for their actions which cause unlawful acts and child perpetrators must be imprisoned and trained in Special Children’s Correctional Institutions. Apart from that, social, economic, mass media (which is influenced by electronic media), and parental factors contribute to teenager committing illegal acts of theft. The judge then made a decision in case number 1/Pid.Sus-Anak/2023/PN BPP. It is appropriate to apply Article 363 paragraph (1) to 3 in conjunction with Article 65 paragraph (1) of the Criminal Code, but the sentence received by the child is too light, even thought this minor is protected, the criminal sanctions given should not be too light so that the child gets a deterrent effect, because the child has committed theft many times, causing disturbance to resident and harming other people.